2021
DOI: 10.1039/d0qo01291b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative nucleophilic alkoxylation of nitrobenzenes

Abstract: Oxidative nucleophilic aromatic substitution for hydrogen of nitroaromatics with potassium alkoxides derived from primary, secondary or tertiary alcohols in the presence of oxygen was achieved. Mechanistic investigations suggest the formation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 8 When in electrophilic variant the rearomatization step usually runs spontaneously, 4 attack of nucleophile on nitroarene at the position occupied by hydrogen gives Meisenheimer-type adduct. 9 Two general routes to transform such adducts into the desired substitution products were developed: oxidative rearomatization 10 and vicarious nucleophilic substitution (VNS), where the nucleophile possesses a leaving group (e.g., halogen; Scheme 1 , top). 11 …”
mentioning
confidence: 99%
“… 8 When in electrophilic variant the rearomatization step usually runs spontaneously, 4 attack of nucleophile on nitroarene at the position occupied by hydrogen gives Meisenheimer-type adduct. 9 Two general routes to transform such adducts into the desired substitution products were developed: oxidative rearomatization 10 and vicarious nucleophilic substitution (VNS), where the nucleophile possesses a leaving group (e.g., halogen; Scheme 1 , top). 11 …”
mentioning
confidence: 99%
“…From the resultant crude mixture, ethyl ether 4 , which seems to be generated via a C–O bond formation at the ortho-position of chloride, was obtained in a 35% yield with a 36% recovery of 1-chloro-3-nitrobenzene 1 . A method for methyl ether syntheses at the same position using a large excess of KOMe was reported by Suzuki and co-workers in 2000, and recently Beier and co-workers reported that tert -butyl ether formation at the same position proceeded effectively with a bubbling of oxygen gas at −78 °C . After extensive effort, we found that an addition of 18-crown-6-ether into a mixture of 1-chloro-3-nitrobenzene 1 and ethanol 2A in DMF achieved etherification at the ipso-position of a nitro group to afford ethyl ether 3 in a 56% yield with a 32% recovery of 1-chloro-3-nitrobenzene 1 .…”
Section: Resultsmentioning
confidence: 54%
“…A method for methyl ether syntheses at the same position using a large excess of KOMe was reported by Suzuki and co-workers in 2000, 7 and recently Beier and coworkers reported that tert-butyl ether formation at the same position proceeded effectively with a bubbling of oxygen gas at −78 °C. 8 After extensive effort, we found that an addition of 18-crown-6-ether into a mixture of 1-chloro-3-nitrobenzene 1 and ethanol 2A in DMF achieved etherification at the ipsoposition of a nitro group to afford ethyl ether 3 in a 56% yield with a 32% recovery of 1-chloro-3-nitrobenzene 1. Similar to our previous method, the sequence for the addition of the reagents was crucial for this etherification (see Figure S1 in the Supporting Information); the addition of a solution of t-BuOK in THF into a mixture of aryl halide, an alcohol, and 18-crown-6-ether in DMF at 0 °C was the most effective.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At present, there are several hypotheses for the mechanism of oxidation, but conclusive experiments are lacking. While some proposals consider oxidation by the nitroarene substrate, other studies support atmospheric oxygen as the oxidant. ,, …”
mentioning
confidence: 99%